GST AND INDIAN FEDERALISM: NEGOTIATING CENTRAL AUTHORITY AND STATE AUTONOMY - Singh, Dhananjay Kumar; Singh, Binod Pratap (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Goods and Services Tax (GST) introduced in 2017 is one of the seminal fiscal reforms in post-independence India. GST sought to create a single, common market by removing a fractured system of state-level indirect taxes and, in the process, prevent double taxation and eventually improve the economies of scale and productivity of businesses. The reform also changed the nature of India’s federal architecture, prompting questions about the balance between central authority and state autonomy. Using the perspective of fiscal federalism, this paper analyses the changes that the introduced GST has brought to the area of financial dependency and political negotiation surrounding the transfer of taxing powers from the states to the Centre. Relying on secondary statistics from the Reserve Bank of India’s reports, the Ministry of Finance’s publications, the GST Council proceedings, and existing academic studies, the study highlights three main findings. Firstly, even though the GST has rationalized tax compliance and expanded the tax base, it has also concentrated substantial tax powers, weakening states’ fiscal autonomy. Second, while the mechanism for compensating states had been designed to avoid vagaries in state revenues, it has bred dependency in the long run, as emerged so sharply during the COVID-19 crisis when late transfers exposed the underbelly of states. Third, the GST Council was envisaged as a forum of collaboration but exhibits both collaboration and asymmetry, in the sense that the Centre has more power to impose its will. The paper demonstrates that the GST has been contributing to national economic integration and infringes on the autonomy of states. Reform to preserve India’s federal balance involves compensation being paid in a timely manner, the threshold or the need for the financial consent of the states for compensation being reduced and flexibility being provided to more and less fiscally capable states and to differing stages of economic development.